2009 16th IEEE International Conference on Image Processing (ICIP) 2009
DOI: 10.1109/icip.2009.5413642
|View full text |Cite
|
Sign up to set email alerts
|

Towards automatic tree crown detection and delineation in spectral feature space using PCNN and morphological reconstruction

Abstract: The application of object-based approaches to the problem of extracting vegetation information from images requires accurate delineation of individual tree crowns. This paper presents an automated method for individual tree crown detection and delineation by applying a simplified PCNN model in spectral feature space followed by post-processing using morphological reconstruction. The algorithm was tested on high resolution multi-spectral aerial images and the results are compared with two existing image segment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…The aim of segmentation is, therefore, to detect and delineate all tree crowns from images while eliminating other image regions. We have developed an automatic tree crown detection and delineation algorithm by utilizing spectral features in a pulse coupled neural network followed by post-processing using morphological reconstruction [6]. Although the automatic segmentation is satisfied from visual assessment, decomposition of tree clusters is occasionally poor.…”
Section: Object-based Color and Texture Feature Extractionmentioning
confidence: 99%
“…The aim of segmentation is, therefore, to detect and delineate all tree crowns from images while eliminating other image regions. We have developed an automatic tree crown detection and delineation algorithm by utilizing spectral features in a pulse coupled neural network followed by post-processing using morphological reconstruction [6]. Although the automatic segmentation is satisfied from visual assessment, decomposition of tree clusters is occasionally poor.…”
Section: Object-based Color and Texture Feature Extractionmentioning
confidence: 99%
“…Considering the spectral properties of vegetation, particular NIR band can be very helpful to detect trees. Li et al employed a simplified pulse-coupled neural network (PCNN) that uses spectral features as input, postprocessed using morphological reconstruction (Li, Hayward, Zhang, Liu, & Walker, 2009). The algorithm has been shown to outperform both JSEG (Deng & Manjunath, 2001) and TreeAnalysis (Erikson, 2003) in tree crown segmentation, but the primary error source is the undersegmentation of tree clusters due to the crown overlap.…”
Section: Automated Data Processingmentioning
confidence: 99%
“…In this study, the algorithm developed by Li et al [23] is used for the detection and delineation of tree crowns, as it has been shown to outperform both JSEG [19] and TreeAnalysis [24] in these applications. The algorithm employs a simplified pulse-coupled neural network (PCNN) that uses spectral features as input, postprocessed using morphological reconstruction.…”
Section: A Vegetation Detectionmentioning
confidence: 99%